-3.7(x-5.3)-5.3(7x-2.4)=-53.35

Simple and best practice solution for -3.7(x-5.3)-5.3(7x-2.4)=-53.35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3.7(x-5.3)-5.3(7x-2.4)=-53.35 equation:


Simplifying
-3.7(x + -5.3) + -5.3(7x + -2.4) = -53.35

Reorder the terms:
-3.7(-5.3 + x) + -5.3(7x + -2.4) = -53.35
(-5.3 * -3.7 + x * -3.7) + -5.3(7x + -2.4) = -53.35
(19.61 + -3.7x) + -5.3(7x + -2.4) = -53.35

Reorder the terms:
19.61 + -3.7x + -5.3(-2.4 + 7x) = -53.35
19.61 + -3.7x + (-2.4 * -5.3 + 7x * -5.3) = -53.35
19.61 + -3.7x + (12.72 + -37.1x) = -53.35

Reorder the terms:
19.61 + 12.72 + -3.7x + -37.1x = -53.35

Combine like terms: 19.61 + 12.72 = 32.33
32.33 + -3.7x + -37.1x = -53.35

Combine like terms: -3.7x + -37.1x = -40.8x
32.33 + -40.8x = -53.35

Solving
32.33 + -40.8x = -53.35

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-32.33' to each side of the equation.
32.33 + -32.33 + -40.8x = -53.35 + -32.33

Combine like terms: 32.33 + -32.33 = 0.00
0.00 + -40.8x = -53.35 + -32.33
-40.8x = -53.35 + -32.33

Combine like terms: -53.35 + -32.33 = -85.68
-40.8x = -85.68

Divide each side by '-40.8'.
x = 2.1

Simplifying
x = 2.1

See similar equations:

| 8(n+3)=9n+3-6 | | 39k^4-9k^3/4 | | 3/5(7x+11+6x) | | 8(3)+3(0)= | | (-2x+3)=25 | | -4(m+5)= | | 2+8j= | | 5x-4(0)=15 | | 9x-2=7x+34 | | 5(3+.08y)-4y=15 | | 6-9/6*3+5*3 | | -5=4x^2-x | | 3a-17=4 | | 6-9/6/3+5*3 | | 7p^2+7p-7=0 | | 175-6=6x+19 | | 3x+12x=105 | | 2(-2)+9(1)= | | 6-9*6/3+5*3 | | 8x+3(1)=-13 | | 6x-5y=-1 | | 3z+2=8 | | 6+17d=13d+18 | | 8(2.5+-4.5y)+3y=-13 | | (6-j)(6+J)= | | -132x-7x=8x+18 | | x+(x+13823)=119453 | | -3x+5y=12 | | 320+8x=7208-220x | | 3(6+5y)=2(-5+5Y) | | 105-5x=9x+2 | | (3/16+5/9)*24/30 |

Equations solver categories